2017
DOI: 10.4103/1735-1995.199087
|View full text |Cite
|
Sign up to set email alerts
|

The association between gallstone disease and plaque in the abdominopelvic arteries

Abstract: Background:The aim of this study was to assess the atheromatous plaque, in the abdominopelvic arteries as a marker of cardiac risk in patients with or without gallstone disease (GD).Materials and Methods:A total of 136 patients were enrolled in this cross-sectional study. Forty-eight patients had GD and the remaining 88 patients did not. The presence or absence of gallstones was noted during abdominal ultrasonography while vascular risk factors such as plaque formation, intima-media thickness, plaque calcifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…The association between GD and CVD may due to a shared metabolic pathway involving cholesterol and other pathophysiological features. Low HDL level is known to increase risk of CVD morbidity and mortality 32 and has been shown to play a role in the development of GD 33 . One study suggests that insulin-like growth factor one (IGF-1) is involved in gallbladder emptying and may have an anti-atherosclerotic effect, which suggests that low plasma levels of IGF-1 may result in both GD and CHD 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between GD and CVD may due to a shared metabolic pathway involving cholesterol and other pathophysiological features. Low HDL level is known to increase risk of CVD morbidity and mortality 32 and has been shown to play a role in the development of GD 33 . One study suggests that insulin-like growth factor one (IGF-1) is involved in gallbladder emptying and may have an anti-atherosclerotic effect, which suggests that low plasma levels of IGF-1 may result in both GD and CHD 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this phenomenon is unknown, but we speculate that it may be related to the following factors. Low HDL levels contribute to the development of GD 33 and CVD, peak total cholesterol levels occur later in men than in women, and HDL levels decrease in postmenopausal women. Diabetes increases the risk of GD 43 and death from CHD 44 , and the incidence of diabetes in women is higher than in men.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high HDL serum was found not to contribute to the formation of gallstones. Another study conducted by Serin et al (2017) showed that low HDL levels are known to play a role in the formation of gallstones [35]. Studies in China have also shown that TC, TG, and LDL levels are risk factors for gallstones, while HDL is a protective factor [36].…”
Section: K Serum Cholesterolmentioning
confidence: 99%
“…The possible pathogenic mechanisms for AD/AN is similar to that of CVD, such as inflammation, degradation of extracellular matrix and apoptosis of vascular smooth muscle cell. 21–23 GD has been shown positively related to abdominopelvic atherosclerosis, 24 and it can be found in 5%–20% of patients with an abdominal aortic aneurysm. 25 In an old study, gallstones were detected in 42 of 865 patients (4.9%) with abdominal AN.…”
Section: Introductionmentioning
confidence: 99%